THE LEARNING CULTURALLY ACCEPTED INCLUSIVE DEVELOPMENT MODEL FOR PERSONS WITH DISABILITIES IN INDONESIA - Irwanto Irwanto; Abdul Mujib; Firmansyah Firmansyah; Eriando Rizky; Widya Prasetyanti (Jurnal Perkotaan, 2019)
In rapid national development, persons with disabilities (PWD) are often lack behind due to lack of policy undertaking that accommodate their limitations and enabling their capacities and strengths. CBR model has been developed by WHO to empower PWD so that they are enabled to participate and contribute in their community as a equel members of the society. This study is reported as a lessons learned from two inclusive disability-based NGO in the districts of Cirebon and Tegal-Slawi. Leaders were funded by Leprosy Research Institute to identify sustained Community Based Organizations (CBOs) in Java and to learn the implementation of CBR principles and inclusive practices. Their journey found only some evidence of CBOs that adopt and implement CBR principles. The lessons learned are used to direct the future development of their respective organizations.